Enhanced Visible-Light Photocatalytic Degradation of Amoxicillin using TiO2-Cu/N with Copper Sourced from Electroplating Wastewater - Suwondo, Kusuma Putri; Wahyuni, Endang Tri; Aprilita, Nurul Hidayat; Jafaar, Nur Farhana; Alharissa, Early Zahwa (Pandawa Institute, 2026)
The growing prevalence of pharmaceutical contaminants, particularly amoxicillin (AMX), in aquatic environments poses serious threats to both ecosystems and public health. Addressing this issue requires the development of efficient photocatalysts capable of degrading such pollutants under visible-light irradiation. This study explores the enhanced photocatalytic degradation of AMX under visible light using copper and nitrogen co-doped titanium dioxide (TiO₂-Cu/N) synthesized utilizing copper recovered from electroplating wastewater. Comprehensive characterization through XRD, UV-Visible DRS, and TEM demonstrated that a Cu doping level of 0.60%, combined with 30% nitrogen co-doping and calcination at 500 °C, resulted in the most significant enhancement in photocatalytic activity under visible-light irradiation, attributed to the most effective bandgap narrowing. Notably, the TiO₂-Cu/N photocatalyst with optimized composition exhibited superior physicochemical properties and photocatalytic performance compared to its singly doped counterparts. The optimal condition of the AMX degradation was achieved using 100 mg of TiO₂-Cu/N to treat 100 mL of a 20 mg/L AMX solution at pH 6 under 2 h of visible-light irradiation, which was 90%. Furthermore, the Cu dopant in the TiO₂-Cu/N matrix remained stable during the photocatalytic process, as evidenced by the sustained activity even after three consecutive cycles. Additionally, the use of radical scavengers confirmed that hydroxyl radicals (•OH) were the predominant reactive species responsible for the degradation of amoxicillin. These findings highlight the promising potential of utilizing industrial wastewater as a dopant source for the sustainable development of high-performance photocatalysts in water treatment applications.